Ekologo-funktsionalnye the reactions, the rizosfernymicrobic communities associated with plants in the soil polluted by oil hydrocarbons (Experimental biology, 2015)
Data on determination of number of microorganisms are provided in this article rizosfer and ризопланы the plants which have been grown up on hydrocarbons of oil, and is established that the maintenance of microorganisms of all ekologo-physiological groups of plants was 1-2 orders higher in comparison with the rizosfery.
Keywords: oil; rizosfera; rizoplan; plants; numbers